Exploiting Gene Expression Variation to Capture Gene-Environment Interactions for Disease - Idaghdour, Youssef; Awadalla, Philip (Frontiers in Genetics, 2013)
Gene-environment interactions have long been recognized as a fundamental concept in evolutionary, quantitative and medical genetics. In the genomics era, study of how environment and genome interact to shape gene expression variation is relevant to understanding the genetic architecture of complex phenotypes. While genetic analysis of gene expression variation focused on main effects, little is known about the extent of interaction effects implicating regulatory variants and their consequences on transcriptional variation. Here we survey the current state of the concept of transcriptional gene-environment interactions and discuss its utility for mapping disease phenotypes in light of the insight gained from genome-wide association studies of gene expression.